Kesenian Ching Pho Ling Di Daerah Purworejo Jawa Tengah Cerminan Budaya Pisowanan - Nanik Sri Prihatini (Mudra Jurnal Seni Budaya, 2008)
pisowanan in the perfomance of Ching Pho Ling, is a phenomenon sosio-kultural that is a demang report duty in its power region. To do the pisowanan, demang followed by the guard to show the spirit of pregnant patriotism assess the struggle, faithfulness, independence, togetherness, and others. In pisowanan of is in form of pageant carry arms to keep safety. Besides also simple music to eliminate tired during of journey. From the pageant form become the artistic idea source of performance in the functioning Ching Pho Ling as look oning/ entertainment amusement society. Creativity of there are at development move the, accompaniment and its cloth. This artistry is very concerning because omiting the single exist in Regency Purworejo, but still eksis. So that require to get the serious attention from local government.